Chat Bot News Analysis to Support Education Services Using Neural Network - Khamidatullailiyah, Yayang; Crysdian, Cahyo; Fatchurrohman, Fatchurrohman (International Journal of Information Systems and Technology, 2025)
During the Covid-19 pandemic, all learning is held online, so all lecture activities up to student administration must be done online. To make it easier for students to obtain information about academics and administration, a chatbot feature is needed which can provide information while communicating two-way to students as users. Chatbots can provide services practically, quickly, and responsively. In order for the chatbot to provide answers that match user expectations, the question sentences that enter the system must be classified properly and correctly. This study applies the Neural Network method to classify answers on chatbots. Neural Networks are used in research methods because they can build models easily and can be used to classify text with a high level of accuracy. To measure the performance of the chatbot system in providing appropriate answers, an evaluation is carried out by calculating the accuracy, precision, recall, and f-measuring values ​​using a confusion matrix. The results of the study show that the Neural Network method built on the chatbot system in classifying answers can run well with an accuracy value of 99.21%, precision of 88.09%, recall of 88.09%, and f-measure of 88.09%.